Hambatan Linguistik dan Nonlinguistik Ragam Lisan yang Dialami oleh Penutur Asing Berlatar Belakang Bahasa Korea - Eva Leydyana (Universitas Sultan Ageng Tirtayasa, 2021)
This research is motivated by the obstacles of foreigners in speaking Indonesian in the fields of linguistics and nonlinguistics. This study aims to (1) describe the form of errors in the field of sentences, and (2) to describe nonlinguistic barriers that include aspects of culture and motivation. The data were provided by observing methods with tapping techniques and in-depth interviews. The advanced technique used is the note-taking technique. The data analysis technique was carried out using the equivalent method with the basic technique of sorting the determinants and advanced techniques of comparative links. From this study it was found that (1) sentence errors occurred in sentence structure including functions and categories, and (2) nonlinguitic barriers that included cultural and motivational aspects.